Recipient CTLA-4*CT60-AA genotype is a prognostic factor for acute graft-versus-host disease in hematopoietic stem cell transplantation for thalassemia - Orrù, Sandro (Elsevier/North-Holland, 2012)
Polymorphisms of the cytotoxic T-lymphocyte antigen-4 gene (CTLA-4) have been associated with autoimmune diseases and it has recently been reported that donor genotypes correlate with the outcome of allogeneic hematopoietic stem cell transplantation in leukemia patients. With the aim of confirming this finding in thalassemia patients, we investigated the influence of genotype distribution of 3 CTLA-4 gene polymorphisms in 72 thalassemia patients and their unrelated donors. A significant association was observed for recipient CT60-AA genotype and onset of grade II–IV (63.2% vs 24.5%; p = 0.001) and grade III–IV (36.4% vs 7.6%; p = 0.005) acute graft-versus-host disease (aGVHD). The same association was observed for the 88-base-pair allele of the CTLA-4 (AT)n polymorphism, which was determined to be in complete linkage disequilibrium with the CT60 A allele. Multinomial Cox regression demonstrated that this association was independent of CT60 donor genotypes or other risk factors (p = 0.016; hazard ratio = 2.8). Our data confirm that the genetic variability in CTLA-4 is an important prognostic factor for aGVHD and suggest that some of the risk factors for this complication are generated by recipient cells that persist after the myeloablative conditioning regimen.